Back to the future? the place of the religious ‘other’ in Ismail Gasprinsky’s Islamic utopia - Mignon, L (Taylor & Francis, 2024)
In 1906, Ismail Gasprinsky (1851–1914), a Crimean Tatar intellectual with ties to the Russian and the Ottoman intelligentsia published his novel The Muslims of the Land of Serenity [Darürrahat Müslümanları], one of the earliest utopian texts in a Turkic language. The narrative uncovers a secret land beyond the Sierra Nevada in Andalusia where some Muslims, having fled after the fall of Grenada in 1492, set up the ideal Muslim state preserving the memory of Islamic Spain over the centuries. This paper discusses factors in the Ottoman literary context that influenced the broad reception of the novel beyond Muslim communities and highlights influences on Gasprinsky from the Ukraine and Russia. After examining the complexities surrounding the religious ‘other’ and its relationship with the external world in Gasprinsky’s utopia, the paper concludes with reflections on the religious ‘other’ contributing to discussions on religious pluralism and freedom within utopian societies.